Aspergillus-Associated Endophenotypes in Bronchiectasis - Jaggi, Tavleen Kaur; Ter, Soo Kai; Mac Aogáin, Micheál; Chotirmall, Sanjay H. (Seminars in Respiratory and Critical Care Medicine, 2021)
Bronchiectasis is a chronic condition of global relevance resulting in permanent and irreversible structural airway damage. Bacterial infection in bronchiectasis is well studied; however, recent molecular studies identify fungi as important pathogens, either independently or in association with bacteria. Aspergillus species are established fungal pathogens in cystic fibrosis and their role is now increasingly being recognized in noncystic fibrosis bronchiectasis. While the healthy airway is constantly exposed to ubiquitously present Aspergillus conidia in the environment, anatomically damaged airways appear more prone to colonization and subsequent infection by this fungal group. Aspergilli possess diverse immunopathological mechanistic capabilities and when coupled with innate immune defects in a susceptible host, such as that observed in bronchiectasis, it may promote a range of clinical manifestations including sensitization, allergic bronchopulmonary aspergillosis, Aspergillus bronchitis, and/or invasive aspergillosis. How such clinical states influence “endophenotypes” in bronchiectasis is therefore of importance, as each Aspergillus-associated disease state has overlapping features with bronchiectasis itself, and can evolve, depending on underlying host immunity from one type into another. Concurrent Aspergillus infection complicates the clinical course and exacerbations in bronchiectasis and therefore dedicated research to better understand the Aspergillus-host interaction in the bronchiectasis airway is now warranted.
Keywords: noncystic fibrosis bronchiectasis; Aspergillus; endophenotypes; fungi; mycobiome